Aktualisasi Amanat Agung di Era Masyarakat 5.0 - Paulus Purwoto; Asih Rachmani Endang Sumiwi; Alfons Renaldo Tampenawas; Joseph Christ Santo (Sekolah Tinggi Teologi Intheos Surakarta, 2021)
Abstract. Society 5.0 is the concept of a new life order that focuses on humans and based on digital technology to support human work. Meanwhile, the Church has the task to carry out the Great Commission of Christ according to Matthew 28:18-20. The problem is how to implement the Great Commission of Christ in this 5.0 society era. The method used in this study is grammatical and lexical study of Matthew 28:18-20. Through this study, it could be concluded that the actualization of the Great Commission of Christ requires new innovations, from previously on-site-based missions to digital missions. Missionaries are required to have capabulity in mission activities innovation through digital technology.Abstrak. Masyarakat 5.0 adalah konsep tatanan kehidupanbaru yang berfokus pada manusia dan berbasiskan teknologi digitaluntuk mendukung pekerjaan manusia.Sedangkan Gereja memiliki tugas untuk melaksanakan Amanat Agung Kristus berdasarkan Matius 28:18-20.Problemnya adalah bagaimanakah implementasi Amanat Agung Kristus di era masyarakat 5.0 ini. Metode yang digunakan dalam kaijian ini adalah studi gramatikal dan leksikal Matius 28:18-20. Melalui kajian ini dapat disimpulkan bahwa aktualisasi Amanat Agung Kristus menuntut inovasi baru, dari sebelumnya misi berbasis on site menuju digital mision.Misionaris dituntut untuk memiliki kemampuan berinovasi dalam aktivitas misi melalui teknologi digital.